Differential reactivity of SARS‐CoV‐2 S‐protein T‐cell epitopes in vaccinated versus naturally infected individuals - Daniel J Browne; Pauline Crooks; Corey Smith; Denise L Doolan (Clinical & Translational Immunology)
Abstract Objectives Vaccine‐induced protective immunity against SARS‐CoV‐2 has proved difficult to sustain. Robust T‐cell responses are thought to play an important role, but T‐cell responses against the SARS‐CoV‐2 spike protein (S‐protein), the core vaccine antigen, following vaccination or natural infection are incompletely understood. Methods Herein, the reactivity of 170 putative SARS‐CoV‐2 S‐protein CD8+ and CD4+ T‐cell peptide epitopes in the same individuals prior to vaccination, after COVID‐19 vaccination, and again following subsequent natural infection was assayed using a high‐throughput reverse transcription‐quantitative PCR (HTS‐RT‐qPCR) assay. Results The profile of immunoreactive SARS‐CoV‐2 S‐protein epitopes differed between vaccination and natural infection. Vaccine‐induced immunoreactive epitopes were localised primarily into two extra‐domanial regions. In contrast, epitopes recognised following natural infection were spread across the antigen. Furthermore, T‐cell epitopes in naïve individuals were primarily recognised in association with HLA‐A, while natural infection shifted epitope associations towards HLA‐B, particularly the B7 supertype. Conclusion This study provides insight into T‐cell responses against the SARS‐CoV‐2 S‐protein following vaccination and subsequent natural infection.